HUBUNGAN KUALITAS KOMUNIKASI PIMPINAN DENGAN TINGKAT KEPUASAN KERJA KARYAWAN DI ANDI POULTRY SHOP BANGAK - Prabowo, Erix (Transformasi, 2015)
The research is research quantitative by using the method research a survey of is eksplanatif.As for the result of obtained in this research be: ( 1 ) based on product moment there is apositive connection significant and strong enough .( 2 ) based on a partial correlation knownthat the position is a significant while salary has a negative correlation but significant .Basedon the results of the analysis can be concluded that the quality of employees communicationimpact on satisfaction work .Position strengthen links while salary is weakened relations .Salary can weakened the relationship between ualitas employees communication on the levelof satisfaction work because a lot of factors affect.Key Words : the quality of communication upward, employees communication, satisfactionwork.